TO UNDERSTAND THE IDEA OF OCCIDENTALISM: WESTERN STUDY THROUGH THE EASTERN PERSPECTIVE - Arlie Nurdiani (Jurnal Ilmiah Pesantren, 2019)
Occidentalism is the idea of the Egyptian renewal character Hassan Hanafi. This idea is to understand the West through the Eastern perspective. So as long as we know the efforts of orientalist to understand the Eastern through their perspectives. Therefore, it is important to note that the importance of the occidentalism is to observate, review and study the West. So, the main purpose of occidentalism is to study the West through the eastern perspective. This is to elimenate Western superiority and restore the eastern confidence. The researcher use the research methods by submitting sources and analyze it. The problem of occidentalism stems from the needs of orientalists to understand Islam and ots people various purposes. In this written, the writer try to describe the meaning, tasks and the aim of occidentalism and also it’s history. This idea is expected not to stop at the boundaries of discourse, but also there is an on going study effort by understanding how the way of occidentalism in studying Western traditions.